Long-term evaluation of uterine fibroid embolisation using MRI perfusion parameters and patient questionnaires: preliminary results - Sadick, Maliha; Leithold, Leonie; Weiß, Christel; Tuschy, Benjamin; Schönberg, Stefan; Zöllner, Frank G. (BMC medical imaging, 2022)
Uterine fibroid embolisation (UFE) is an established treatment method for symptomatic uterine myomas. This study evaluates the efficacy of UFE using objective magnetic resonance imaging (MRI) data for size and perfusion analysis as well as patient questionnaires assessing fibroid-related symptoms.